2003
DOI: 10.6028/nist.ir.6946
|View full text |Cite
|
Sign up to set email alerts
|

Potential benefits of smart refrigerant distributors, final report

Abstract: Prepared for the Under ART1 2 1 -CR Program Contract Number 605-20050 AIR-CONDITIONING AND REFRIGERATION TECHNOLOGY INSTITUTE Use of Non-SI Units in a Non-NIST Publication It is the policy of the National Institute of Standards and Technology to use the International System of Units (metric units) in all of its publications. However, in North America in the HVAC&R industry, certain non-SI units are so widely used instead of SI units that it is more practical and less confusing to use measurement values for cus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…(a) Wang(A) [5] (b) Wang(C) [5] (c) Wang(E) [5] (d) Wang(F) [5] (e) Wang(G) [5] (f ) Ge(A) [6] (g) Ge(B) [6] (h) Kuo(A) [4] (i) Kuo(B) [4] (j) Ge [7] (k) Liu [2] (l) Domanski [8] Figura 15: Ejemplos de circuitos validados.…”
Section: Validación De Los Resultadosmentioning
confidence: 99%
“…(a) Wang(A) [5] (b) Wang(C) [5] (c) Wang(E) [5] (d) Wang(F) [5] (e) Wang(G) [5] (f ) Ge(A) [6] (g) Ge(B) [6] (h) Kuo(A) [4] (i) Kuo(B) [4] (j) Ge [7] (k) Liu [2] (l) Domanski [8] Figura 15: Ejemplos de circuitos validados.…”
Section: Validación De Los Resultadosmentioning
confidence: 99%
“…Studies regarding the benefits by control of individual superheat have also been conducted. Payne and Domanski (2003) showed experimentally that the performance degradation due to a non-uniform airflow could be recovered to within 2% of the original cooling capacity at uniform airflow conditions. Kim et al (2009a) studied benefits of upstream vs. downstream control of individual channel superheat on a fin-and-tube five channel R410A heat pump numerically.…”
Section: Air Flowmentioning
confidence: 94%
“…Flow maldistribution in fin-and-tube evaporators has been shown to decrease the performance of the evaporator and the system both experimentally (Payne and Domanski, 2003) and numerically (Kaern et al, 2011b;Kim et al, 2009b). Both air side and refrigerant side effects may cause flow non-uniformities, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Payne and Domanski (2003) showed that the capacity dropped as much as 41% and 32% for two different fin-and-tube evaporators due to variable superheat values between the circuits when circuit pressure drops were induced and the overall superheat was fixed at 5.6…”
Section: Introductionmentioning
confidence: 99%